Coccidioidal Peritonitis Masquerading as Acute Appendicitis - Jose Garcia-Corella; Mania Mgdsyan; Essam Hashem; Shikha Mishra; Alexandra W. Elias; Rasha Kuran (Annals of Internal Medicine: Clinical Cases)
Coccidioidomycosis is a fungal infection resulting from the inhalation of arthroconidia produced by the genus Coccidioides. Most encounters with this fungus result in asymptomatic or undiagnosed pulmonary disease. A smaller percentage of individuals develop symptoms, typically respiratory. A small number have disseminated (extrathoracic) disease. A previously healthy woman presented with right lower quadrant abdominal pain, with computed tomography scan findings raising suspicion for acute appendicitis. Laparoscopic examination revealed miliary-type peritoneal nodules throughout the abdominal cavity, and endosporulating spherules pathognomonic for Coccidioides were identified on histologic examination. Treatment with triazoles led to satisfactory recovery, followed by relapse. We present an unusual presentation of disseminated coccidioidomycosis presenting as abdominal pain mimicking acute appendicitis.